Uporabna vrednost podatkov spletnih zajemov - Kragelj, Matjaž (Knjižnica, 2017)
The Legal Deposit Act imposes to the National and University Library the concern and rights for capturing, preserving and providing access to online publications, web sites, and other content to library users. In 2015, the Library started the first capture of Slovenian .si internet domain. The domain addresses were provided by ARNES (the Academic and Research Network of Slovenia). The article focuses on the importance of covering the web content due to the deterioration of daily web domains. In addition to covering and activities to ensure the conservation of web contents, the paper also covers the subject of how to obtain information from unstructured content (documents on the web). The article shows some examples and applications to capture specific information from a variety of online documents (scraping), like the price of a selected item in a particular web store in order to inform the end user about the best offer on the market. The major part of the article is devoted to the analysis of captured web content and the possibility of scaling and ranking the vocabulary derived from web documents. The algorithms and statistics for marking and document ranking in a mass of web content can help transform the web archive from a passive database to the environment that creates the added value of data integration, finding similarities within a web archive data and the data from the outside of a web archive.
Keywords: identifikacija bibliografskih odnosov; web archives; term frequency; spletni arhivi; inverse document frequency; frekvenca pojavljanja; data scraping; tf-idf; web harvesting; luščenje podatkov; spletni zajemi; .si domain; domena.si